The Crooked Nose: A Practical Guide to Successful Management. Issue 4 (29th March 2022) - Block, Lisa; Pfaff, Miles J.; Harris, Alexandria; Goldstein, Jesse A.; Losee, Joseph E.
Abstract : Learning Objectives: After studying this article, the participant should be able to: (1) Preoperatively evaluate the patient with a crooked nose. (2) Develop a comprehensive preoperative plan specific to the patient. (3) Effectively "deconstruct" and rebuild the crooked nose to address both aesthetic and functional concerns. (4) Use postoperative techniques to maximize outcomes. Summary: Correction of the crooked nose requires a detailed understanding of the relevant surgical anatomy, identification of the deforming forces—both intrinsic and extrinsic—contributing to the deformity, and knowledge of techniques needed to effect the desired change. This continuing medical education article takes the reader through the evaluation and formulation processes to develop a patient-specific plan and provides surgical pearls necessary to get the best results possible. Most importantly, this article emphasizes the need to treat the crooked nose as a reconstructive rather than routine aesthetic operation.